117k views
13 votes
Solve the literal equation for x

Solve the literal equation for x-example-1
User Imochoa
by
5.1k points

2 Answers

9 votes

Answer:

Are this Form 1 question?

User Virtuoso
by
6.0k points
10 votes

Answer:

see explanation

Explanation:

(1)

y = 5x - 7x , that is

y = - 2x ( divide both sides by - 2 )

x = -
(1)/(2) y

(2)

mx - r = y ( add r to both sides )

mx = y + r ( divide both sides by m )

x =
(y+r)/(m)

(3)

2x + 3y = 10 ( subtract 2x from both sides )

3y = 10 - 2x ( divide both sides by 3 )

y =
(10-2x)/(3)

(4)

5x - 3y = 4 ( subtract 5x from both sides )

- 3y = 4 - 5x ( divide both sides by - 3 )

y =
(4-5x)/(-3) ( multiply numerator/ denominator by - 1 , to 'tidy up' )

y =
(5x-4)/(3)

User Felix Zumstein
by
5.1k points